Non-coding RNAs in Cardiac Intercellular Communication - Videira, Raquel Figuinha; da Costa Martins, Paula A. (Frontiers in Physiology, 2020)
Intercellular communication is the process whereby molecular information is transferred from cell to cell in order to maintain tissue or organ homeostasis and its dysregulation due to either changes on the vehicle or the cargo information, may contribute to pathological events, such as cardiac pathological remodeling. Extracellular vesicles (EVs), namely exosomes, are double-layer vesicles secreted by cells to mediate intercellular communication, both locally and systemically. EVs can carry different types of cargo, including non-coding RNAs (ncRNAs), which, in turn, are major regulators of both physiological and pathological processes. ncRNAs transported in EVs are functionally active and trigger a cascade of processes in the recipient cells. Upon cardiac injury, exosomal ncRNAs can derive from and target different cardiac cell types to initiate remodeling cellular and molecular events such as hypertrophic growth, cardiac fibrosis, endothelial dysfunction and inflammation, altogether contributing to cardiac dysfunction and eventually heart failure. Recent data advocate exosomal ncRNAs as crucial players in the process of cardiac pathological remodeling and indicate that modification of ncRNA profiles in EVs can attenuate cardiac dysfunction, suggesting exosomal ncRNAs as potential new therapeutic targets. Here, we review the current research on the role of ncRNAs in intercellular communication, in the context of cardiac pathological remodeling.